Changes in Bone Mineral Density During and After Lactation in Ugandan Women With HIV on Tenofovir‐Based Antiretroviral Therapy. (26th August 2020) - Nabwire, Florence; Prentice, Ann; Hamill, Matthew M; Fowler, Mary Glenn; Byamugisha, Josaphat; Kekitiinwa, Adeodata; Goldberg, Gail R
ABSTRACT: Antiretroviral therapy (ART) in people living with human immunodeficiency virus (HIV) is associated with bone loss, but data are limited in lactation, when physiological bone mineral mobilization is occurring. This research charted changes in areal bone mineral density (aBMD) during and after lactation in Ugandan women with HIV (WWH) initiated onto ART in pregnancy, compared to women without HIV (REF). One‐hundred WWH on tenofovir‐based ART and 100 REF were enrolled in pregnancy. Lumbar spine (LS), total hip (TH), and whole‐body‐less‐head (WBLH) aBMD were measured by dual‐energy X‐ray absorptiometry (DXA) at 2, 14, and 26 weeks of lactation, and at 3 months postlactation. The primary outcome was the difference between groups in mean percent change in LS aBMD between 2 and 14 weeks. Statistical analysis was performed in hierarchical repeated measures ANOVA models that corrected for multiple testing. Median age was 23.4 (IQR, 21.0 to 26.8) years. WWH had lower body weight. aBMD decreased in both groups during lactation, but WWH had greater decreases at TH (2‐to‐26 weeks: WWH [ n = 63] −5.9% [95% CI, −6.4 to −5.4] versus REF [ n = 64] −4.3% [95% CI, −4.8 to −3.8]; group*time point interaction p = .008). Decreases in LS aBMD were similar in WWH and REF (2‐to‐26 weeks: −2.0% [95% CI, −2.5 to −1.5]), although there was a tendency toward a smaller decrease in WWH between 2 and 14 weeks (WWH [ n = 77] −1.8% [95% CI, −2.2 to −1.4] versus REF [ n = 69] −2.9% [95% CI, −3.3 to −2.5]; group*time point interaction p = .08). Postlactation, LS aBMD was higher relative to week 2 in both groups. TH and WBLH aBMD did not return to week 2 values in WWH but did in REF (TH postlactation versus week 2: WWH [ n = 61] −3.1% [95% CI, −3.6 to −2.6]; REF [ n = 29] +0.1% [95% CI, −0.9 to +1.1]). These data show accentuated bone loss during lactation and only partial skeletal recovery by 3 months postlactation in Ugandan WWH on tenofovir‐based ART. Studies are ongoing to understand longer‐term consequences for bone health. © 2020 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.